Analysis of open-hole-tension plates made of short fibre thermoplastic and reinforced with continuous fibre tailored inserts. (March 2023) - Arnaut, Katharina; Dimassi, M Adli; Romahn, Bernd; Atilla, Ufuk; Herrmann, Axel S
In the present paper, the influence of tailored load introduction inserts applied to a bolt-loaded open-hole injection plate with different short glass fibre content is investigated. The tailored load introduction inserts made with a Tailored Fibre Placement (TFP) process, as well as open-hole injection plates without an insert were considered as reference samples. The samples were tested under tensile bolt-loading. The influence of the TFP-inserts on the load bearing properties of the open-hole injection plates was investigated. The test results show a huge increase of the load-carrying ability of the short-glass-fibre specimens when TFP-inserts are integrated. Moreover, the damage tolerance was dramatically improved as the specimens with integrated TFP-inserts did not fail abruptly and a residual strength higher than the strength of the test specimen without insert could be observed. However, the strength of the test specimen with integrated insert did not exceed the strength of the insert itself in most cases.